Respuesta :
The product of the expression [tex]\rm \dfrac{\dfrac{2y}{y-3} }{\dfrac{4y-12}{2y+6}}\\\\\\[/tex] is [tex]\rm \dfrac{(y^2+3y)}{(y^2-6y+9)}\\[/tex].
What is the product?
In mathematics, the term 'product' refers to the answer to a multiplication problem.
The product of the given expression is determined in the following steps given below.
[tex]\rm =\dfrac{\dfrac{2y}{y-3} }{\dfrac{4y-12}{2y+6}}\\\\\\=\dfrac{2y}{y-3}\times \dfrac{2y+6}{4y-12}\\\\= \dfrac{2y \times 2y + 2y \times 6}{y(4y-12)-3(4y-12)}\\\\=\dfrac{4y^2+12y}{4y^2-12y-12y+36}\\\\=\dfrac{4y^2+12y}{4y^2-24y+36}\\\\=\dfrac{4(y^2+3y)}{4(y^2-6y+9)}\\\\ =\dfrac{(y^2+3y)}{(y^2-6y+9)}\\[/tex]
Hence, the product of the expression [tex]\rm \dfrac{\dfrac{2y}{y-3} }{\dfrac{4y-12}{2y+6}}\\\\\\[/tex] is [tex]\rm \dfrac{(y^2+3y)}{(y^2-6y+9)}\\[/tex].
To know more about the product click the link given below.
https://brainly.com/question/15029466